The Dual Approach to Frodo Baggins’ Characterization: Direct and Indirect Methods in Tolkien’s The Fellowship of the Ring - Febrianti, Nabilah Tri; Assiddiqi, Hasbi; Listiani, Toneng (Universitas Muhammadiyah Kotabumi, 2025)
This analysis examines the connection between social aspects and the characterization of Frodo Baggins in The Fellowship of the Ring by J.R.R. Tolkien. In novels, as in any other form of art, the storyline and characters are intricately woven together. This work of research will show how social issues affect Frodo's evolution as a character. The analysis have been found using descriptive qualitative approach, which means that out of 51 instances of characterization associated with determination, 12 were direct and 39 were indirect. Furthermore, the inquiry reveals that while 42 instances where a connection of characterization of Frodo and the main theme of adventure is found, for 9 of the instances direct portrayal and for 33 instances indirect portraying of determination fighting overwhelming odds are did. Thus, this study affirms that Frodo's characterization is deeper than adventure, but rather courage and sense of responsibility. Frodo's journey depict not only the struggle to triumph, but also depicts the inner turmoil, altruism, and grit that is embedded in the violence of searching for the self. This analysis assists in further understanding of Frodo Baggins as a reluctant hero, supporting the Claim that he is a depiction of human struggle against adversities.